2000
DOI: 10.1259/bjr.73.865.10721319
|View full text |Cite
|
Sign up to set email alerts
|

Application of draft European Commission reference levels to a regional CT dose survey.

Abstract: A survey of CT doses in Northern Ireland in the period between October 1995 and March 1997 was carried out. The survey included all but one of the 10 scanners in use at the time, and, additionally, two others that were replacement machines. The method used was to study standard protocols and calculate doses to the NRPB mathematical phantom, so that a direct comparison could be made with other surveys carried out in a similar fashion elsewhere. The survey addressed the patient radiation dose but not image quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 2 publications
3
23
1
1
Order By: Relevance
“…CT examinations in 1994 in Germany made up 4.2% of the total number of radiological examinations but contributed 37.8% of the entire effective radiation dose to the German population [9]. Similar results have been reported in the UK, where it is estimated that CT makes up 4% of the total radiological examinations and contributes 40% of the effective radiation dose to the population [43,44].…”
Section: Computer Tomography Radiation Dosesupporting
confidence: 54%
See 1 more Smart Citation
“…CT examinations in 1994 in Germany made up 4.2% of the total number of radiological examinations but contributed 37.8% of the entire effective radiation dose to the German population [9]. Similar results have been reported in the UK, where it is estimated that CT makes up 4% of the total radiological examinations and contributes 40% of the effective radiation dose to the population [43,44].…”
Section: Computer Tomography Radiation Dosesupporting
confidence: 54%
“…The phantom results should verify that the dose used for the study is adequate to provide reliable quantitative measures of emphysema while keeping the radiation dose as low as possible. If only measures of lung density are required recent research suggests that 140 kVp and 20 mas may be adequate for accurate results with an expected effective radiation dose to the subject of 0.7 mSv [44].…”
Section: Computed Tomography Image Acquisitionmentioning
confidence: 99%
“…However, this is not surprising because the significant variations in the CTDI w among different clinical sites have been reported with the same CT scanner model and scanning protocols. [46][47][48] If the organ doses are scaled by the actual measurement of the CTDI w under a CT scanner of interest, it will substantially improve the accuracy of the resulting organ doses. However, the measurement is not feasible in most cases of the organ dose reconstruction for patients examined in the past ͑as in radiation epidemiology studies͒.…”
Section: Discussionmentioning
confidence: 99%
“…8 Effective dose calculation is the best available predictor of the stochastic risk of a given radiological examination as it estimates or calculates the dose of organs. 9 Study by Wade JP et al 10 concluded that, the effective dose for the head scan is considerably less than that for the trunk scans, even though the CTDI values for head scan are much higher. This is because fewer of the radiosensitive organs are irradiated.…”
Section: Introductionmentioning
confidence: 99%